Uncommon Gram-Negative Opportunists as Drivers of Cancer-Related Immunomodulation: The Virulence Machinery of Aeromonas, Shewanella, and Morganella Species - Aziz, Salah Naji; Al-zubaidy, Kawakib I.; Muhson Badar, Fatima (Asian Pacific Journal of Cancer Biology, 2026)
Immunosuppression and tissue destruction related to cancer provide a niche of permissible colonization by opportunistic bacteria, although the role of uncommon gram-negative pathogens in tumor-associated immune modulation has not been studied in detail. New findings point to Aeromonas, Shewanella, and Morganella organisms that were historically considered either environmental or low-virulence provirulence organisms as potential active mediators of cancer-related immunomodulation by having highly complex virulence systems. These bacteria have a repertoire of pathogenic determinants such as type III and type VI secretion systems, iron acquisition mechanisms, endotoxin reorganization, biofilm formation, and outer membrane vesicle release that allow them to withstand antagonistic tumor microenvironment and a direct contact with host immune pathways. Along with the cancer environment, these opportunists can contribute to immune dysregulation through cytokine profile distortion, phagocytic dysfunction, persistent inflammation, and immune evasion. Their redox-adaptive capacities and metabolic flexibility also favor their survival in hypoxic environments, nutrient-scarcity and oxidative stress, which are the hallmarks of solid tumors. Most importantly, the communication between these bacteria and tumor-related immune cells, including macrophages and neutrophils can strengthen pro-tumorigenic inflammation and suppress efficient antitumor immunity. Simultaneously, antimicrobial resistance characteristics and stress-regulated virulence determinants increase their clinical usefulness in immunocompromised cancer patients. The current review has identified the mechanistic roles of the Aeromonas, Shewanella and Morganella species as unorthodox yet biologically important mediators of immune homeostasis to cancer. Their virulence mechanisms and contact with the host can reveal new biomarkers of infection-mediated tumor pathogenesis and be useful in combination therapy with microbial-specific factors and immune dysfunction in cancer management.